(untitled) (Journal of Engineering, 2018)
At present, smooth movement on the roads is a matter which is needed for each user. Many roads, especially in urban areas geometrically improved because of the number of vehicles increase from time to time. In this research, Highway capacity software, HCS, 2000, will be adopted to determine the effectiveness of roundabout in terms of capacity of roundabout, delay and level of service of roundabout. The results of the analysis indicated that the Ahmed Urabi roundabout operates under level of service F with an average control delay of 300 seconds per vehicle during the peak hours. The through movements of Alkarrada- Aljadiriya direction (Major Direction) represent the heaviest traffic volumes in Ahmed Urabi intersection. The use of underpass to serve the through movements in Alkarrada-Aljadiriya direction will lead to release the traffic volume in the Ahmed Urabi intersection with a rate 51 % .After the adoption of the proposed geometric design, it will operate at LOS B in the design year (2037). The proposed circulatory roadway width for the roundabout is 16m and the required number of lanes equal to three lanes for each side of the underpass and four lanes for all the approaches of the roundabout.